19 Brain imaging after tbi. Issue 8 (13th July 2017) - Sharp, David J
Abstract : Professor David Sharp is a consultant neurologist and was awarded one of the UKs first round of National Institute of Health Research (NIHR) Professorships. He is the Head of the Centre for Restorative Neuroscience at Imperial and Scientific Director of the Imperial College Clinical Imaging Facility. His research programme aims to improve clinical outcome after traumatic brain injury (TBI), focusing on common cognitive impairments in domains such as memory and attention. He uses advanced neuroimaging to investigate the effect of brain injury on brain network function and the effects of inflammation and neurodegeneration after TBI. His NIHR research programme will use changes in network function to guide the development of novel treatment strategies for cognitive impairment. He leads TBI research within the Royal British Legion Centre for Blast Injury Studies and collaborates with The Royal Centre for Defence Medicine to study the effects of blast exposure military personnel. Diffuse axonal injury after traumatic brain injury (TBI) produces neurological impairment by disconnecting brain networks. This structural damage can be mapped using diffusion MRI, and its functional effects can be investigated in large-scale intrinsic connectivity networks (ICNs). Here, we review evidence that TBI substantially disrupts ICN function, and that this disruption predicts cognitive impairment. We focus on two ICNs—the salience network and the default mode network. The activity of these ICNs is normally tightly coupled, which is important for attentional control. Damage to the structural connectivity of these networks produces predictable abnormalities of network function and cognitive control. For example, the brain normally shows a 'small-world architecture' that is optimised for information processing, but TBI shifts network function away from this organisation. The effects of TBI on network function are likely to be complex, and we discuss how advanced approaches to modelling brain dynamics can provide insights into the network dysfunction. We highlight how structural network damage caused by axonal injury might interact with neuroinflammation and neurodegeneration in the pathogenesis of Alzheimer disease and chronic traumatic encephalopathy, which are late complications of TBI. Finally, we discuss how network-level diagnostics could inform diagnosis, prognosis and treatment development following TBI. Reference: . David J Sharp, et al. Network dysfunction after traumatic brain injury. Nature Reviews Neurology2014;10:156–166. Published online 11 February 2014.